1998
DOI: 10.1542/peds.101.3.335
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/II Study of the Protease Inhibitor Ritonavir in Children With Human Immunodeficiency Virus Infection

Abstract: The oral solution of ritonavir has potent antiretroviral activity as a single agent and is relatively well tolerated by children when administered alone or in combination with zidovudine or didanosine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
3
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 27 publications
2
37
3
2
Order By: Relevance
“…The immediate treatment effects are most apparent with an improvement in weight and AMC; however, there was a trend toward a delayed response in height as well. The results of this study confirm previous research on the positive effect of PIs as a component of HAART in the reduction of viral load 2,16,17,[27][28][29] and with a larger cohort, confirm preliminary reports that suggest a positive effect of PIs on growth. 16,18,19,27,28,30,31 Other markers of nutrition, such as lean body mass, improved as well.…”
Section: Discussionsupporting
confidence: 91%
“…The immediate treatment effects are most apparent with an improvement in weight and AMC; however, there was a trend toward a delayed response in height as well. The results of this study confirm previous research on the positive effect of PIs as a component of HAART in the reduction of viral load 2,16,17,[27][28][29] and with a larger cohort, confirm preliminary reports that suggest a positive effect of PIs on growth. 16,18,19,27,28,30,31 Other markers of nutrition, such as lean body mass, improved as well.…”
Section: Discussionsupporting
confidence: 91%
“…In clinical trials, HAART has been shown to suppress viral load (VL) to less than the limits of detection and to increase the CD4+ T lymphocyte percentage in many İletişim/Correspondence to: Nasir Tajure Wabe, Jimma University P.O. Box 251 1480, Jimma, ETHIOPIA Tel: +251 911 68 0576 patients (14,15), with good outcomes overall (16,17). Results from observational studies suggest that at least 73.5% of patients initiating HAART achieve complete virological suppression within 6 months (18), but 9%-45% of patients do not experience an appropriate increase in their CD4 cell counts in the short term (19,20).…”
mentioning
confidence: 99%
“…While an increase in total CD4+ T lymphocytes is readily detectable, the ability to regenerate immunocompetent T-cell populations remains unresolved (21). Some clinical trials have demonstrated that the regenerated T cells consist predominantly of the memory (CD45RO+) type (14), while others have shown repopulation of naive (thymus-dependent, CD45RA+) T cells as well (22).…”
mentioning
confidence: 99%
“…1 To date, data regarding the disposition and drug interactions of nelfinavir (NFV) and other PIs in the pediatric population are limited. [2][3][4][5][6][7] We report the unique pharmacokinetic parameters of NFV dosed at a target of 27 to 33 mg/kg orally three times daily (TID), in the absence and presence of the nonnucleoside reverse transcriptase inhibitor (NNRTI) nevirapine (NVP), and dosed at a target of 55 mg/kg twice daily (BID) in clinically stable, antiretroviral-experienced patients who were aged 8 months to 16 years and enrolled in a large Pediatric AIDS Clinical Trials Group Protocol (PACTG) 377. PACTG 377 was designed to evaluate new combinations of potent antiretroviral agents.…”
mentioning
confidence: 99%